2016
DOI: 10.1099/jmm.0.000292
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil sensitivity varies among oral micro-organisms

Abstract: 5-Fluorouracil (5-FU), a commonly used chemotherapeutic agent, often causes oral mucositis, an inflammation and ulceration of the oral mucosa. Micro-organisms in the oral cavity are thought to play an important role in the aggravation and severity of mucositis, but the mechanisms behind this remain unclear. Although 5-FU has been shown to elicit antibacterial effects at high concentrations (>100 µM), its antibacterial effect at physiologically relevant concentrations in the oral cavity is unknown. This study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…These findings are consistent with the conclusion of Cohen et al () who found that 5‐FU is primarily bacteriostatic and Vanlancker et al () who reported a decreased growth rate of Streptococcus salivarius and Pseudomonas aeruginosa exposed to 5‐FU. Others have reported more profound effects including the complete inhibition of E. coli and S. aureus at concentrations as low as 0·5 mg l −1 and 1 mg l −1 respectively (Bodet et al ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with the conclusion of Cohen et al () who found that 5‐FU is primarily bacteriostatic and Vanlancker et al () who reported a decreased growth rate of Streptococcus salivarius and Pseudomonas aeruginosa exposed to 5‐FU. Others have reported more profound effects including the complete inhibition of E. coli and S. aureus at concentrations as low as 0·5 mg l −1 and 1 mg l −1 respectively (Bodet et al ).…”
Section: Resultssupporting
confidence: 92%
“…Cytotoxic chemotherapeutic agents used to treat malignant neoplasms have been shown to have off target effects on prokaryotic organisms; similarly some antimicrobials have anti‐tumour activity (Soo et al ; Markowska et al ). Antibacterial effects have been reported for bleomycin (Bodet et al ; Xu et al ), gemcitabine (Sandrini et al ; Jordheim et al ), 5‐fluorouracil (5‐FU) (Cohen et al ; Rogers and Perkins ; Hamilton‐Miller ; Bodet et al ; Vanlancker et al ), doxorubicin (Hamilton‐Miller ; Bodet et al ; Peiris and Oppenheim ; Panda et al ; Feng et al ) and methotrexate (Hamilton‐Miller ; Kruszewska et al ). Unsurprisingly, the spectrum of antibacterial effect for each drug varies between bacterial species (Bodet et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent patient studies have looked at overall diversity of oral flora and shifts during chemotherapy [6] to determine relationships with oral mucositis. In vitro models of oral keratinocytes have also been used to demonstrate how microbes impact healing [7,8], as well as the functional changes to the microbes themselves during exposure to irradiation [9,10]. The field has also been advancing rapidly in the area of intestinal mucositis, where microbial dysbiosis, measured in easily accessible fecal samples, has led researchers to postulate that gut microbiome composition can be used as a surrogate marker for changes leading to diarrhea [11].…”
Section: Microbiome and Host Immune Responsementioning
confidence: 99%
“…Two commensal species including S. salivarius and L. salivarius were significant enriched after the chemotherapy. According to the previous studies, these two species appeared to be highly resistant to 5-FU [36], which maybe the main driver for a community dysbiosis. We hypothesized that if 5-FU was responsible for the dysbiosis changes seen during chemotherapy, then depleted taxa should be susceptible to the drug while the enriched species would be resistant to 5-FU.…”
Section: Discussionmentioning
confidence: 88%